Resposta:
[tex]\textsf{letra C}[/tex]
Explicação passo a passo:
[tex]\sf{A \widehat CB = 180^{\circ} - (\alpha + \beta )}[/tex]
[tex]\sf{A \widehat CB = 180^{\circ} - (30^{\circ} + 60^{\circ} )}[/tex]
[tex]\sf{A \widehat CB = 180^{\circ} - 90^{\circ}}[/tex]
[tex]\sf{A \widehat CB = 90^{\circ}}[/tex]
[tex]\sf{D \widehat CA = C \widehat AB}[/tex]
[tex]\sf{D \widehat CB = D \widehat CA + A \widehat CB }[/tex]
[tex]\sf{D \widehat CB = 30^{\circ} + 90^{\circ} }[/tex]
[tex]\boxed{\boxed{\sf{D \widehat CB = 120^{\circ} }}}[/tex]